Using Experimental Models to Decipher the Effects of Acetaminophen and NSAIDs on Reproductive Development and Health - Boizet-Bonhoure, Brigitte; Déjardin, Stéphanie; Rossitto, Moïra; Poulat, Francis; Philibert, Pascal (Frontiers in Toxicology, 2022)
Nonsteroidal anti-inflammatory drugs (NSAIDs), such as aspirin (acetylsalicylic acid), diclofenac and ibuprofen (IBU), and analgesic drugs, such as acetaminophen (APAP, or paracetamol), are widely used to treat inflammation and pain. APAP and IBU are over-the-counter drugs and are among the most commonly taken drugs in the first trimester of pregnancy, even in combination. Furthermore, these drugs and their metabolites are released in the environment, and can be frequently detected in wastewater, surface water, and importantly in drinking water. Although their environmental concentrations are much lower than the therapeutics doses, this suggests an uncontrolled low-dose exposure of the general population, including pregnant women and young children, two particularly at risk populations. Epidemiological studies show that exposure to these molecules in the first and second trimester of gestation can favor genital malformations in new-born boys. To investigate the cellular, molecular and mechanistic effects of exposure to these molecules, ex vivo studies with human or rodent gonadal explants and in vivo experiments in rodents have been performed in the past years. This review recapitulates recent data obtained in rodent models after in utero or postnatal exposure to these drugs. The first part of this review discusses the mechanisms by which NSAIDs and analgesics may impair gonadal development and maturation, puberty development, sex hormone production, maturation and function of adult organs, and ultimately fertility in the exposed animals and their offspring. Like other endocrine disruptors, NSAIDs and APAP interfere with endocrine gland function and may have inter/transgenerational adverse effects. Particularly, they may target germ cells, resulting in reduced quality of male and female gametes, and decreased fertility of exposed individuals and their descendants. Then, this review discusses the effects of exposure to a single drug (APAP, aspirin or IBU) or to combination of different endocrine disruptors during early embryogenesis, and the consequences on postnatal gonadal development and adult reproductive health. Altogether, these data may increase medical and public awareness about these reproductive health concerns, particularly in women of childbearing age, pregnant women, and parents of young children.